2013
DOI: 10.1002/jbmr.1984
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin antibody stimulates bone regeneration after experimental periodontitis

Abstract: The reconstruction of large osseous defects due to periodontitis is a challenge in regenerative therapy. Sclerostin, secreted by osteocytes, is a key physiological inhibitor of osteogenesis. Pharmacologic inhibition of sclerostin using sclerostin-neutralizing monoclonal antibody (Scl-Ab) thus increases bone formation, bone mass and bone strength in models of osteopenia and fracture repair. This study assessed the therapeutic potential of Scl-Ab to stimulate alveolar bone regeneration following experimental per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(147 citation statements)
references
References 36 publications
5
140
0
2
Order By: Relevance
“…Sclerostin antibody administered to rats with a critical-sized femoral defect and mice with a non-criticalsized femoral defect showed earlier healing, complete union, and physiologic maturation of the defect 71,72 . Similar conclusions can be drawn from the rat model of experimental periodontitis, in which sclerostin antibody treatment increased alveolar bone regeneration and filled substantial oral bone defects 73 .…”
mentioning
confidence: 58%
“…Sclerostin antibody administered to rats with a critical-sized femoral defect and mice with a non-criticalsized femoral defect showed earlier healing, complete union, and physiologic maturation of the defect 71,72 . Similar conclusions can be drawn from the rat model of experimental periodontitis, in which sclerostin antibody treatment increased alveolar bone regeneration and filled substantial oral bone defects 73 .…”
mentioning
confidence: 58%
“…Thus, we assume that anti-sclerostin antibody is able to stimulate bone regeneration after experimental periodontitis, and even for periodontitis which sometimes may be caused by orthodontic treatment or obesity. (28,29). In addition, a single-dose placebo-controlled randomized clinical trial of anti-sclerostin antibody has suggested that further clinical investigations of sclerostin inhibition as a potential therapeutic strategy would be justified for patients in whom increased bone formation is necessary (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is secreted by osteocytes and acts on cells along the endosteal surfaces (58,59), and inhibits the binding of Wnts to LRP5 (3,60). The inhibitory effects of SOST on Wnt signaling and bone formation can be ameliorated by a monoclonal antibody, which has been shown to increase bone mass in postmenopausal women in clinical trials and improve fracture healing and osteogenesis imperfecta in animal models (14,16,17). Hence, it has garnered a lot of attention for its promise as a bone anabolic drug.…”
Section: A Possible Mechanism For the Bone Anabolic Effect By Inhibitingmentioning
confidence: 99%
“…These findings further underscore the importance of studying the identity and role of Wnt-producing cells in bone development. Furthermore, the antibody blocking SOST is effective in ameliorating catabolic skeletal diseases, like osteogenesis imperfecta (14) and osteoporosis in rats (15), and improves fracture healing (16). Currently, the anti-SOST antibody is undergoing clinical trials in the treatment of osteoporosis and the preliminary results are promising (17).…”
mentioning
confidence: 99%